Evaluating burden and quality of life among caregivers of patients receiving peritoneal dialysis - Kang, Augustine (2019)
Peritoneal dialysis (PD) is advocated as treatment of choice for most end-stage renal disease (ESRD) patients, including elderly and frail patients. It typically requires caregiver involvement to support care at home. The purpose of this study was to examine changes in burden and quality of life (QOL) in caregivers of prevalent PD patients over 12 months. Data were collected in 44 caregivers of PD patients (mean age 38.4 ± 6.3 years; 60% female) in Singapore at baseline and 12 months. Measures included demographics, the Lay Care-Giving for Adults Receiving Dialysis (LC-GAD), Zarit Burden Interview (ZBI), and the World Health Organization Quality of Life instrument (WHOQOL-BREF). Paired t-tests indicate a significant decrease in task-related aspects of caregiving (p = 0.04), particularly in relation to personal hygiene (p < 0.01), over time. Cognitive aspects of caregiving remained unchanged. Perceived burden, however, significantly increased (p < 0.01), with significantly more caregivers reporting moderate to severe caregiver burden at follow-up (28%) relative to baseline (13%; p < 0.01). There was a significant reduction in psychological health (under WHOQOL) (p = 0.01). Study findings indicate an increase in caregiver burden and a reduction in psychological health despite a reduction in task-related aspects of caregiving, supporting a further exploration of the “wear-and-tear” hypothesis among this population. Intervention strategies are needed.